Analisis Willingness To Pay Pengguna Jasa Bus Rapid Transit (Brt) Banjarbakula Dan Faktor-Faktor Yang Mempengaruhinya - Nadya Dwi Yuniarty; Khairi Pahlevi (PPJP ULM, 2020)
This study aims to: (1) analyze the willingness to pay (WTP) users ofBanjarbakula Bus Rapid Transit (BRT) services (2) determine the effect of education,income, and the number of family members on the WTP value of Bus Rapid Transit (BRT)respondents Banjarbakula.This type of research is quantitative research with the method used that is usingthe Stated Preference method and multiple linear regression analysis. The variables usedare education, income, and number of family members. The data used are primary datataken from the source, namely Banjarbakula BRT users and the Transportation Office ofSouth Kalimantan Province.The results showed the average willingness to pay respondents amounted to Rp5,720. If there is an increase in quality, the average willingness to pay the respondentbecomes Rp10,180. The factors of education, income, and the number of family memberstogether affect the WTP value of Banjarbakula BRT services users.